2010
DOI: 10.1364/oe.18.013122
|View full text |Cite
|
Sign up to set email alerts
|

On femtosecond micromachining of HPHT single-crystal diamond with direct laser writing using tight focusing

Abstract: We investigate the formation of diversiform micro-/nano-structures in High-Pressure High-Temperature (HPHT) synthetic single-crystal diamond by tight-focusing 200 fs regeneratively amplified Ti: Sapphire laser pulses centered at lambda = 800 nm. Ablated samples of synthetic single crystal nanodiamond and their acetate replicas are analyzed using scanning electron microscopy (SEM). Using pulse energies that are significantly above the threshold for permanent change, it is shown from this work that amplified fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
0
26
0
2
Order By: Relevance
“…Actually, in the bulk the whole pulse energy is deposited onto the sample compared to only a small energy fraction in the case of nanodiamonds, which have an absorption cross-section smaller than the focused beam area. Therefore, optical breakdown can take place in the diamond plate after the multi-photon absorption and the electron-hole pair formation [26]. This breakdown effect consists of an avalanche ionization in which the seed electrons are driven by the laser field and then cause secondary collisional ionization [27].…”
Section: Quenching Nanodiamond Photoluminescence With 1064 Nm Pulsed mentioning
confidence: 99%
“…Actually, in the bulk the whole pulse energy is deposited onto the sample compared to only a small energy fraction in the case of nanodiamonds, which have an absorption cross-section smaller than the focused beam area. Therefore, optical breakdown can take place in the diamond plate after the multi-photon absorption and the electron-hole pair formation [26]. This breakdown effect consists of an avalanche ionization in which the seed electrons are driven by the laser field and then cause secondary collisional ionization [27].…”
Section: Quenching Nanodiamond Photoluminescence With 1064 Nm Pulsed mentioning
confidence: 99%
“…LIPSS have been already fabricated on diamond and morphologically investigated by other groups [13][14][15][16][17]. To our knowledge, only Kononenko et al [18] reported on optical transmission behaviour as a function of laser fluence for fs-laser-induced microstructures in bulk natural and CVD diamond.…”
Section: Introductionmentioning
confidence: 99%
“…With higher intensity, the laser could be too violent that it would damage much more diamond sample and even NV centers. Different from Ref [30,31]. which showed the multiphoton ionization of carbon atoms in the diamond, here it was the air that was multiphoton-ionized to provide the electrons.…”
Section: Illumination Processmentioning
confidence: 87%